Workplace Incivility Dalam Kaitannya Dengan Organizational Citizenship Behavior Pada Karyawan Hotel - Margaretta, Evelinadela; Elvinawanty, Rianda; Situmeang, Saulina Serpi; Meliala, Enzelin Regina S.; Hartini, Sri (Jayapangus Press, 2026)
The rapid growth of the hotel industry requires organizations to maintain high service quality to remain competitive. Service quality is influenced not only by formal procedures but also by employees’ voluntary behaviors, known as Organizational Citizenship Behavior (OCB), which enhance organizational effectiveness. However, workplace incivility, characterized by low-intensity deviant behavior such as disrespect and disregard among employees, remains prevalent and may undermine positive work attitudes and behaviors. This study aimed to examine the relationship between workplace incivility and OCB among hotel employees. A quantitative correlational design was employed using Pearson’s correlation analysis. The sample consisted of 105 employees of Lake Toba International Hotel selected through purposive sampling. Data were collected using validated workplace incivility and OCB scales and analyzed statistically. The results revealed a strong and significant negative correlation between workplace incivility and OCB (r = −0.733, p < 0.05), indicating that higher levels of workplace incivility were associated with lower levels of OCB. Furthermore, the coefficient of determination (R² = 0.537) showed that workplace incivility accounted for 53.7% of the variance in OCB, demonstrating a substantial contribution. These findings suggest that workplace incivility plays a critical role in reducing employees’ willingness to engage in voluntary, constructive behaviors that support organizational effectiveness and service quality. In conclusion, minimizing workplace incivility through respectful communication, supportive leadership, and positive organizational culture is essential to foster OCB and enhance overall service performance in the hospitality industry. These strategies strengthen employee cooperation, satisfaction, and long-term organizational sustainability and competitiveness in modern hospitality contexts today.